EPCO-07. HYBRID NEURO-GLIAL CELLULAR ARCHITECTURE IN HIGH-GRADE GLIOMA DRIVEN BY H3-G34R MUTATION. (12th November 2021) - Laffy, Julie; Nomura, Masashi; He, Chen; Bussema, Lillian; Slyper, Michal; Hover, Laura; Gritsch, Simon; Regev, Aviv; Baker, Suzanne; Tirosh, Itay; Suva, Mario
Abstract: High-grade gliomas (HGG) with histone H3.3 G34R mutation are rare intractable tumours in the cerebral hemispheres that preferentially affect adolescents and young adults, but have unknown mechanisms of neuroanatomical specificity and tumourigenesis. Here, we performed single-nucleus RNA-sequencing of twenty patient samples, encompassing twelve tumours with G34R mutation and eight H3.3 wildtype HGGs, age- and location-matched. Both classes of HGG were heterogeneous, with malignant cells in multiple states, recapitulating neural and glial developmental trajectories. G34R HGG is distinguished by lack of malignant cells in the oligodendroglial lineage, and aberrant expression of neuronal programs superimposed over cellular states, resulting in hybrid glio-neuronal malignant programs. Singe-cell barcoding supports plasticity between cellular states in HGG with multiple possible transitions. CRISPR-correction of G34R in HGG models followed by scRNA-seq supports that the G34R mutation directly drives these aberrant programs. Our study provides a framework for studying the origin and tumourigenesis of paediatric gliomas.